Performing Out of Limbo: Reflections on Doing Anthropology through Music with Oromo Refugees in Indonesia - Dave Lumenta; Rhino Ariefiansyah; Betharia Nurhadist (Antropologi Indonesia, 2017)
This article is an anthropological reflection on an on-campus collaborative music project between (Ethiopian) Oromo refugees and local Indonesian university teaching staff, students and professional musicians. It follows the way the project evolved from what was initially seen as a simple academic research opportunity and technical assistance for refugees to record their songs into a mutually transformative experience for those involved. It reflects on the process and the way art—as a collaborative practice and non-programmatic form of human engagement—provided new possibilities for the refugees living in transit in Indonesia to explore their talents and possible career opportunities for the future. From an anthropological point of view, the process challenged the various institutionalized binary modes of self-representation, such as ‘host’ and ‘migrant’, ‘researcher’ and ‘informant’, or ‘academic’ and ‘non-academic’, and opened up new possibilities for negotiating and framing relationships between the participants involved.Keywords: refugees, asylum seekers, self-representation, public anthropology, art, Indonesia, Oromo